Strategi Inovatif Dalam Mengelola Keuangan Keluarga: Pengalaman Dari Program KKN di Desa Domas Kabupaten Mojokerto - Rosita Farhat; Nadhifatul Nur Maulani; Sjarief Hidajat (MENGABDI : Jurnal Hasil Kegiatan Bersama Masyarakat, 2024)
Domas Village, located in Mojokerto Regency, faces challenges in family financial management that impact the community's welfare. The Community Service Program (KKN) of UPN "Veteran" East Java aims to provide innovative solutions through financial education for the PKK mothers in the village. The methods used include presentations, discussions, practical workshops, and household mentoring. Through presentations and discussions, participants are given basic knowledge about financial literacy, the importance of saving, and how to create a household budget. Practical workshops help participants practice budgeting and debt management strategies. Household mentoring ensures the implementation of the acquired knowledge. The results of this program show an increase in awareness and knowledge of financial management among PKK mothers, reflected in the increased number of families who start budgeting and saving regularly. Consequently, this program has successfully created sustainable social change in the lives of the local residents